2010
DOI: 10.1111/j.1442-2050.2009.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamine in patients with esophagus resection

Abstract: 17 survivors/8 nonsurvivors; P= 0.607). Daily Multiple Organ Dysfunction Score did not differ significantly between the two groups. The observed inflammatory markers followed the pattern we described without significant difference. Based on our study, the glutamine supplementation that we used had no influence on morbidity, mortality, or postoperative inflammatory response after esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Ten trials [ 19 , 20 , 22 , 40 , 41 , 42 , 43 , 44 , 47 , 48 ], including 900 patients, provided data on postoperative mortality. However, only in four studies at least one event was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten trials [ 19 , 20 , 22 , 40 , 41 , 42 , 43 , 44 , 47 , 48 ], including 900 patients, provided data on postoperative mortality. However, only in four studies at least one event was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The first meta-analysis by Novak et al [ 24 ] was published in 2002 and the second by Zheng in 2006 [ 25 ]. Since than another seven RCTs [ 19 , 22 , 45 , 46 , 47 , 48 , 49 ] have become available in the literature and, therefore, the different conclusions may be justified by the number of trials analyzed. Another two more recent meta-analyses published in 2010 [ 26 ] and 2013 [ 23 ] suggested that glutamine supplementation in this specific cohort of patients was associated with a significant better outcome as measured by postoperative infection rate and LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Marton et al. demonstrated that perioperative glutamine supplementation had no influence on morbidity, mortality, and postoperative inflammatory response after esophagectomy [16]. As little is known of the effects of intravenous amino acid supplementation during recovery from surgical stress on early postoperative period, we assessed the effects of intravenous amino acid supplementation via peripheral veins, following radical esophagectomy for esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed Makay et al 63 Omega-3 Postoperative 30 n.s. Marton et al 65 Glutamine Perioperative 30 Mixed Morlion et al 68 Glutamine Postoperative 29 n.s. Neri et al 70 Glutamine Postoperative 30 n.s.…”
Section: Data Extractionmentioning
confidence: 99%